2021
DOI: 10.1002/jwmg.22120
|View full text |Cite
|
Sign up to set email alerts
|

Landscape Features Fail to Explain Spatial Genetic Structure in White‐Tailed Deer Across Ohio, USA

Abstract: Landscape features influence wildlife movements across spatial scales and have the potential to influence the spread of disease. Chronic wasting disease (CWD) is a fatal prion disease affecting members of the family Cervidae, particularly white‐tailed deer (Odocoileus virginianus), and the first positive CWD case in a wild deer in Ohio, USA, was recorded in 2020. Landscape genetics approaches are increasingly used to better understand potential pathways for CWD spread in white‐tailed deer, but little is known … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(13 citation statements)
references
References 94 publications
2
11
0
Order By: Relevance
“…Twenty‐four studies (13%) provided access to raw data, while only four studies (2%) provided the code necessary to repeat analyses. Two studies (Bauder et al 2021, Crego et al 2021) provided open access to both data and code. Eight studies (4%) indicated that the data were sensitive, and thus did not provide open access.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Twenty‐four studies (13%) provided access to raw data, while only four studies (2%) provided the code necessary to repeat analyses. Two studies (Bauder et al 2021, Crego et al 2021) provided open access to both data and code. Eight studies (4%) indicated that the data were sensitive, and thus did not provide open access.…”
Section: Resultsmentioning
confidence: 99%
“…Twenty-four studies (13%) provided access to raw data, while only four studies (2%) provided the code necessary to repeat analyses. Two studies (Bauder et al 2021, Crego et al 2021 Figure 1. (a) The number of studies published each year that used circuit theory to model connectivity for at least one terrestrial mammal (n = 181 studies).…”
Section: Data and Code Availabilitymentioning
confidence: 99%
“…Individual-based sampling and analysis are widely used in landscape genetics, particularly for organisms that do not show discrete subpopulation structure or are continuously distributed across space (Bauder, Anderson, et al, 2021;Draheim et al, 2018;Laurence et al, 2013). However both necessary and justified.…”
Section: Discussionmentioning
confidence: 99%
“…Forest cover is the most consistent driver of WTD dispersal distances [13], but the effect of landscape features on deer dispersal rates and distances is not always consistent across populations [22]. Bauder et al, [25], for example, found minimal landscape-driven genetic structuring of WTD in Ohio, concluding that landscape features likely do not form a barrier to deer movement in their study area.…”
Section: Introductionmentioning
confidence: 96%